Save the Bank: Centralized Digital Bank — Centralization and Digitalization as Strategic Imperatives - Bing Hu (Journal of World Economy, 2024)
This thesis explores the transformation of traditional banks into centralized digital banking systems as a strategic response to the burgeoning challenges posed by decentralized finance (DeFi) technologies such as blockchain and cryptocurrencies. As these technologies disrupt traditional financial paradigms, offering more direct, efficient, and transparent financial services, traditional banks face increasing pressure to adapt and evolve. This work argues for the necessity and feasibility of centralized digital banking as a comprehensive countermeasure to DeFi. Through a detailed examination of current banking challenges, including inefficiencies in customer service, transaction processing, and compliance, the thesis proposes a model of banking that leverages centralization and digitalization to address these issues. The proposed model not only enhances operational efficiency and customer engagement but also fortifies the banks’ competitive edge in a digital economy. Furthermore, the thesis discusses the long-term implications of such transformations, predicting that centralized digital banks will not only coexist with DeFi platforms but may also lead the financial services industry by adopting innovative technologies that drive customer satisfaction and operational excellence. Recommendations are provided for both banks and policymakers to foster an environment conducive to the development of robust, secure, and customer-focused digital banking services. In summary, this thesis affirms that centralized digital banking is not merely a defensive strategy against the rise of DeFi but a forward-looking approach that will define the future of banking.